Peningkatan Pemahaman Konsep Trigonometri melalui Pembelajaran Discovery Learning - Muh. Afdal Nur; Mas’ud Badolo; Arifuddin Arifuddin (Griya Journal of Mathematics Education and Application, 2026)
This classroom action research aimed to improve students' conceptual understanding of trigonometry through the implementation of the Discovery Learning model. The study was motivated by the low conceptual understanding of students, particularly in explaining concepts, connecting trigonometric concepts, and applying them to various problem-solving situations. The research was conducted in Class X Unggul 3 of SMA Negeri 3 Parepare during the 2025/2026 academic year and involved 32 students. The study employed a mixed-methods approach and was carried out in three cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through conceptual understanding tests, observations, interviews, and documentation. The results showed a consistent improvement in students’ conceptual understanding across all indicators. The average conceptual understanding score increased from 56 in the pre-cycle stage to 68 in Cycle I, 78 in Cycle II, and 88 in Cycle III. Learning mastery also improved from 31.25% in the pre-cycle stage to 56.25% in Cycle I, 78.13% in Cycle II, and 93.75% in Cycle III. These findings indicate that the implementation of the Discovery Learning model contributed to the improvement of students’ conceptual understanding and learning mastery in trigonometry through active engagement in the process of discovering and constructing mathematical concepts.